Advanced Training of Teachers in Innovative Pedagogical Activity - Natalia A. Sergeeva; Natalia A. Yakovleva; Aleksandr V. Kuleshov (ARPHA Proceedings, 2020)
Problem relevance. The education system faces new challenges in re-evaluating goals, functions and content related to social changes. It is worth noting that the modern labor market requires highly qualified mobile specialists, having a high level of educational cognitive motivation and professionally significant personality qualities, able to quickly and effectively respond to critical situations and produce high results. Study goal. The paper highlights the criteria for innovative forms of advanced training of teachers, the stages of their application, a comparative analysis of traditional and innovative approaches to advanced training, as well as current requirements for innovative forms of advanced training organization. It requires a qualitatively different training of teachers, which allows combining the fundamental nature of professional basic knowledge with innovative thinking and a practice-oriented research approach to solving specific educational problems. Materials and methods. The main methods used in the study of the problem are: cognitive-synthesizing (the study of psychological and pedagogical literature on the research problem); theoretical (comparative method, method of design during curricula planning); empirical (surveying, testing, statistical processing of data and results). Practical relevance. The practical relevance of the study lies in the fact that a model of advanced training of teachers has been developed in the context of professional pedagogical activity changes. It can be used by institutions of further professional education as one of the components in the educational process, as well as in development of new ways of organizing advanced training. Results and discussion. The study was conducted among 46 university teachers. The results presented in the paper prove that the advanced training course developed by the authors contributes to a change in attitudes toward professional activity, an understanding of the need for self-development, for the introduction of innovations and the use of new teaching technologies, insufficient or zero experience in applying technological tools. In general, we can conclude that the use of innovative teaching technologies should be systematic, focused and closely associated with the needs of modern teachers.